(3QSGdI ddTjN YR GdOjf CHj YHO GdSdGes - (3YR GdOjf YHO GdYRjR Hf YHO GdSdGe Hf CHh GdbGSe Hf GdMSf GdSdej GdOeTbj, GdYR Hf YHO GdSdGe,J (B660 (3g` s
(3ChdgG (B:s
(3bGd GdTjN aUd ai HjGf CUhd GdfGS eYXe GdfGS s
(3BNQgG (B:s
(3Yf efcQ hGMO HdaX hGMO hdPdc GdJHTjQ hGdEfPGQ HNRf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B21s
(3eUOQ GbJfGA GdCUd (B:s
(3GdGRgQ (B(944) s
Keywords: (3CUhd Gdabgs